POTENSI KAWASAN WISATA ALAM AIR TERJUN TOWE RAMA DESA TOLIBA KECAMATAN TOJO BARAT KABUPATEN TOJO UNA UNA - Rahayu, Rizky; Rukmi, Rukmi; Sustri, Sustri (Jurnal Warta Rimba, 2020)
Tourism has a big role in national development. In Tojo Una-Una District has a lot of natural tourism potential, for example Togean natural tourism which is a very famous tourist attraction both domestically and overseas. The purpose of this study was to identify the Tourism Potential of Towe Rama Waterfall, Toliba Village, West Tojo Subdistrict, Tojo Una Una District. The study was conducted for two months, from June to July 2019, located at Towe Rama Waterfall Tourism Object in Toliba Village, West Tojo Subdistrict, Tojo Una Una District. In this study the method used is a descriptive and qualitative approach based on the Guidelines for the Analysis of Regional Operations of Objects and Attractions of Nature Tourism (ADO-ODTWA) of the Directorate General of PHKA in 2003 with the Assessment of Attraction, Accessibility, Accommodation, and Supporting Infrastructure Facilities in the Tourist Attraction Area Towe Rama Waterfall. Sampling was done by interviewing the local community who know or manage the Towe Rama Waterfall Tourism Object Area in Toliba Village. The number of samples consisting of 31 people is enough to represent the purpose of the study, only the factor that needs to be considered is the representation of the community elements used as the research sample. The results showed that the potential of natural tourism in Towe Rama Waterfall in Toliba Village, West Tojo Subdistrict, Tojo Una Una Regency that has natural beauty that is still very natural, beautiful natural panorama, in addition to tourist attractions, Towe Rama Waterfall located in Toliba Village can be used as a place of research / education for students. The eligibility index of each criterion includes attractiveness of 86.1%, Acceleration of 70.83%, Accommodation 33.3% and Infrastructure Facilities 97.22% of all criteria that with a feasibility level index of 74.25% including the category deserve to be developed as a tourism object.